2007
DOI: 10.1007/s00595-007-3512-x
|View full text |Cite
|
Sign up to set email alerts
|

Staple Line Reinforcement with Fleece-Coated Fibrin Glue (TachoComb) After Thoracoscopic Bullectomy for the Treatment of Spontaneous Pneumothorax

Abstract: The recurrence rate after thoracoscopic bullectomy with fleece-coated fibrin glue was significantly lowered and we consider this procedure to be the treatment of choice for the management of spontaneous pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
0
42
1
Order By: Relevance
“…According to the American College of Chest Physicians (21) and BTS guidelines (4), the preferred approach for prevention of recurrent pneumothorax is still surgical because of lower recurrence rates compared with instillation of sclerosing agents through a chest tube. However, the recurrence rate is still high at 5.9% to 24.5%, even after thoracoscopic stapled bullectomy (Table 5) (18,(22)(23)(24)(25)(26)(27). Therefore, Lee at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the American College of Chest Physicians (21) and BTS guidelines (4), the preferred approach for prevention of recurrent pneumothorax is still surgical because of lower recurrence rates compared with instillation of sclerosing agents through a chest tube. However, the recurrence rate is still high at 5.9% to 24.5%, even after thoracoscopic stapled bullectomy (Table 5) (18,(22)(23)(24)(25)(26)(27). Therefore, Lee at al.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that visceral pleural coverage by cellulose mesh and fibrin glue after thoracoscopic bullectomy was not inferior to mechanical pleurodesis (28). Muramatsu et al demonstrated a significantly reduced recurrence rate after thoracoscopic bullectomy with fleece-coated fibrin glue (TachoComb) (24).…”
Section: Discussionmentioning
confidence: 99%
“…We think fi brosis could function as a mechanical barrier between the bronchial stump and pleural cavity. 13,14) Thus, the prevention of communication between the bronchial stump and the pleural cavity could be mediated by fi brosis and adhesion. Lastly, while many studies support the benefi t of stump coverage, controversy remains concerning which coverage technique should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Association between postoperative bulla neogenesis at the staple line and resected lung weight for primary spontaneous pneumothorax: a retrospective study using the inverse-probability of treatment weighted method in patients grouped according to age considered a factor in promoting PSP recurrence (3,7). In a modification of the original surgical technique, the staple line is reinforced with an absorbable sheet and/or fibrin glue to prevent POBN.…”
Section: Original Articlementioning
confidence: 99%
“…Thus, the reduction of post-therapy recurrence rate is of particular importance. For surgical treatment of PSP, bullectomy, using autosutures under video-assisted thoracoscopic surgery (VATS), is the standard procedure at present (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%